Pengujian Fungsional Website eCampus Universitas Bina Insani Menggunakan Alpha dan Beta Testing - Firdan Margian Ramadhan; Bagas Adi Pratama Wijanarko; Mohamad Ikhsan Haidar; Tri Aji Santoso; Willy Andika Nugraha (PT. Tech Cart Press, 2026)
The eCampus Website of Bina Insani University is an academic information system that provides various services to support students’ academic activities, including login, e-learning, grade information, Study Result Card (KHS) printing, academic transcripts, GPA information, lecture schedules, attendance, learning materials, discussions, assignments, and group assignments. To ensure that the system operates according to user requirements, testing of its functionality and user acceptance is necessary. This study aims to test and evaluate the quality of the Bina Insani University eCampus Website using Alpha Testing and Beta Testing methods. Alpha Testing was conducted using a Black Box Testing approach to examine the main system functions based on predetermined scenarios and test cases. Meanwhile, Beta Testing involved 36 user respondents through a questionnaire consisting of 19 statements to measure user acceptance of the system. The Alpha Testing results show that most functions of the eCampus Website operate according to the requirements and testing scenarios, although several features still require improvement, particularly the Forgot Password feature and one of the functions in the Mata Kuliah menu. The Beta Testing results obtained an actual score of 2,366 out of a maximum score of 3,420, resulting in a user acceptance rate of 69.18%, which falls into the good category. The system functionality aspect received a good assessment, while the user interface aspect received a lower assessment and therefore still requires further development. Based on the testing results, the Bina Insani University eCampus Website is considered suitable for use as a medium to support academic services and is well accepted by users.